To Imagine Equality - Besana, Bruno (Filozofski vestnik, 2016)
The text concerns the role of break and separation within the thought of Jacques Rancière. Many commentators present the philosophy of Rancière as the intersection of aesthetics and politics, but often this relation is still conceived as a synthesis of both within a single philosophical metadiscourse. The author shows how, on the contrary, Rancière insists on conceiving the articulation of this relation between the heterogeneous fields of aesthetics and politics only in a series of singular breaks and separations within both fields. Only these breaks can produce aesthetic effects within politics as much as political effects within aesthetics. Following this perspective, the author sets out the three most important breaks within Rancière’s thought: the break within the heterogeneous fields of aesthetics and politics; the break in aesthetics introduced by singular images; and the break produced within philosophy by the equality of images.